Style & status : selling beauty to African American women, 1920-1975 - Walker, Susannah, 1970- (University Press of Kentucky, 2007)
Examines twentieth-century commercial beauty culture in terms of race and gender. This work demonstrates that while black women's beauty culture often mirrored that of white women in important ways, it remained distinctive because it explicitly articulated racial politics in the United States.